PHARMACOGNOSTICAL STUDY OF OSBECKIA MURALIS NAUDIN. - B, *Binu; Padyana, Subrahmanya; Kumar, Sunil (AYUSHDHARA, 2017)
The plant ‘Nela Nekkarika’ in Kannada, ‘Cherkulathi’ in Malayalam and ‘Cen- Thumbai’ in Tamil is botanically identified as Osbeckia muralis Naudin belongs to the family Melastomaceae. This herb is commonly used by the ethnomedical practitioners of the Dakshina Kannada District of Karnataka State. It is an encouraging ethnomedicine in the respiratory ailments especially in cough. This is an herb endemic to Western Ghats. Some of the practitioners from the foot hills of Western Ghats are using other species of Osbeckia which looks similar to Osbeckia muralis Naudin. None of the classical Ayurvedic literatures had mentioned about this plant. Hence to explore its identity, pharmacognostical study of Osbeckia muralis Naudin is undertaken. For the purpose of standardization, macroscopic, microscopic and powder microscopic studies has been carried out. The morphological study shows that the herb is a 30 cm tall less branched hirsute herb with elliptic shaped leaves tetramerous flowers and purple petals. The microscopic study of the stem and the leaf has been carried out which shows chlorenchyma cells, glandular trichomes, multicellular covering trichomes, calcium oxalate crystals, pallisade parenchyma and spongy parenchyma etc. The powder microscopic study shows multiserriate trichome, glandular trichome, pith parenchyma etc. This study can help for the standardization and authentication of the genuine drug.